THE INFLUENCE OF POLLUTED SOIL AERATION IN THE PROCESS OF IN SITU BIOLEACHING - SUR, Ioana Monica; MICLE, Valer; GABOR, Timea (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The influence of aeration of soils polluted with heavy metals by using Thiobacillus-type microorganisms was studied using soil samples contaminated with heavy metals (Cu 4074 - 7550 mgkg-1, Zn 5870 - 9310 mgkg-1, Cd 36-50 mgkg-1, Pb 15000 - 42890 mgkg-1), from Romplumb, Baia Mare. The variation of the metal concentration extracted by bioleaching and aerated bioleaching was monitored for 16 weeks. The soil samples treated by bioleaching (Cu: 9 - 53%; Zn: 9 - 62%; Cd: 9 - 24%. Pb: 31 - 71%) have obtained a lower efficiency than the soil samples treated by aerated bioleaching (Cu: 34 - 70%; Zn: 36 - 76%; Cd: 17 - 38%. Pb: 44 - 78%), but there are percentage differences between the two processes (Cu: 17 - 27%; Zn: 14 - 27%; Cd: 8 - 14%, Pb: 7 - 13%).